Pb isotope composition of Klyuchevskoy volcano, Kamchatka and North Pacific sediments: Implications for magma genesis and crustal recycling in the Kamchatkan arc - Kersting Annie B.; Arculus Richard J. (Earth and Planetary Science Letters, 1995)
Pb isotope data are used to constrain the chemical contribution of the subducted components in the recycling beneath Klyuchevskoy volcano, the most active volcano in the Kamchatkan arc. The Pb isotope ratios of Klyuchevskoy basalts (206Pb/204Pb= 18.26–18.30, 207/Pb204Pb= 15.45–15.48, 208/Pb204Pb= 37.83–37.91) define a narrow range that falls within the Pacific mid-ocean ridge basalt (MORB) field and are among the least radiogenic island arc basalts measured to date. These data are similar to data from three other Quaternary Kamchatkan volcanoes: Tolbachik, Kumroch-Shish, and Maly Semiachik. In contrast, North Pacific sediments (primarily siliceous oozes) collected parallel to the Kamchatkan trench during Ocean Drilling Program Leg 145, have Pb isotope ratios (206Pb/204Pb= 18.51–18.78, 207Pb/204Pb= 15.56–15.64, 208Pb/204Pb= 38.49–38.75) that are more radiogenic than either the Klyuchevskoy basalts or Pacific MORB. Incorporation of even a small amount of sediment in the source of the Klyuchevskoy magmas would shift the Pb isotope ratios of the erupted basalts from the MORB field to more radiogenic values. The absence of 10Be and elevated Pb isotope ratios in the Kamchatkan volcanic lavas, despite the presence of distinctively radiogenic Pb in the North Pacific sediments makes it unlikely that sediments or sediment-derived fluids are involved in the source magmas beneath Kamchatka. The Kamchatkan arc thus represents an “end-member” whereby little or no sediment is involved in terms of elemental recycling and arc magma genesis. The major and trace elements, Pb, Sr and Nd isotope data of the Kamchatkan basalts are most consistently explained if derived from a fluid-fluxed, peridotitic mantle wedge source, wherein the fluid composition is dominantly controlled by dehydration of altered oceanic crust, imparting a radiogenic 87Sr/86Sr, and MORB-like Pb isotope signature to the mantle source. The erupted Klyuchevskoy lavas preserve a slab signature derived from incompatible elements that are strongly partitioned into the ...